Republic of Uzbekistan : Technical Assistance Report-Report on the External Sector Statistics Mission (November 20-December 1, 2017). (IMF Staff Country Reports; Country Report ;, 2018)
At the request of the Republic of Uzbekistan authorities for technical assistance (TA) on external sector statistics (ESS), and with the support of the Middle East and Central Asia Department (MCD) of the International Monetary Fund (IMF), a mission from the IMF Statistics Department (STA) visited Tashkent from November 20 through December 1, 2017. This was the first TA mission on ESS since the Republic of Uzbekistan Presidential Order of September 12, 2017, 'On Measures to Ensure the Accessibility and Openness of Economic and Financial Data for the Republic of Uzbekistan' was issued.